KEDUDUKAN AKTA PERDAMAIAN YANG DIBUAT DI HADAPAN NOTARIS SEBAGAI ALAT BUKTI DALAM PENYELESAIAN SENGKETA DI TINGKAT BANDING (STUDI KASUS PUTUSAN PENGADILAN TINGGI YOGYAKARTA NOMOR 07/PDT/2010/PTY) - , H M Luthfie ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this research is to find out and describe the status of dead of peace drawn up before a notary as proof of evidence in dispute resolution in appeal proceeding, and to find out and describe causes of the deed of peace drawn up before a notary was not submitted as proof of evidence in appeal proceeding in the case of Judgement of High Court of Yogyakarta Number 07/PDT/2010/PTY. This research is of legal normative and empiric type, which examines researchâs problems out of the existing statutes and their implementation with regard to deed of peace drawn up before a notary and dispute resolution in appeal proceeding. Data gathering method is by library research and field research using document study and semi-structured interview guideline. Current research uses qualitative analysis, which is an analysis based on reality found in the society. Result of this research showed that a deed of peace drawn up before a notary as a form of peace efforts outside the court might serve as perfect proof of evidence provided meet formal and material requirements of authentic deed drawing up as stipulated in Article 1868 KUHPerdata (Indonesian Civil Code) and Articles 15-19 and 38-65 Act Number 30/2004 in conjunction with Act Number 2/2014. In the case in question the deed of peace was not submitted as proof of evidence since one party of the deed of peace is unqualified to be a legal entity according to Act Number 16/2001 in conjunction with Act Number 28/2004 so that the deed did not meet one formal requirement according to Article 1320 in conjunction with Article 1330 in conjunction with Article 1852 KUHPerdata. In this case studied, although the deed of peace drawn up before a notary met formal requirements of authentic acte drawing up according to Article 1 KUHPerdata, Articles 15-19 and Articles 38-65 Act Number 30/2004 in conjunction with Act Number 2/2014, but material of the deed (which is the peace agreement) has a formal flaw.